2015
DOI: 10.1007/s10803-015-2474-x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Repetitive Behaviours in Young Children with Autism Spectrum Disorder (ASD): Pilot Randomised Controlled Trial of a New Parent Group Intervention

Abstract: Early intervention for autism spectrum disorder (ASD) tends to focus on enhancing social-communication skills. We report the acceptability, feasibility and impact on child functioning of a new 8 weeks parent-group intervention to manage restricted and repetitive behaviours (RRB) in young children with ASD aged 3-7 years. Forty-five families took part in the pilot RCT. A range of primary and secondary outcome measures were collected on four occasions (baseline, 10, 18 and 24 weeks) to capture both independent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…Interventions specifically focused on RRBs in children with ASD and other neurodevelopmental disorders are rare [54, 55]. Our findings suggest self-regulation as a viable intervention target as measured by EC.…”
Section: Discussionmentioning
confidence: 81%
“…Interventions specifically focused on RRBs in children with ASD and other neurodevelopmental disorders are rare [54, 55]. Our findings suggest self-regulation as a viable intervention target as measured by EC.…”
Section: Discussionmentioning
confidence: 81%
“…10,14 In the context of NDDs/NPDs, however, RRBs adversely impact multiple aspects of functioning 15 and are therefore important targets for clinical intervention. 16 Distinguishing clinically significant behavior from typical behavior requires a clearer understanding of the normal variability of a broader range of RRBs across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ability to reduce the insistence on sameness and to increase flexibility can have highly beneficial effects for improving daily life functioning of affected individuals. Given that effective treatment approaches targeting RRB across neurodevelopmental disorders are currently lacking [Grahame et al, 2015;NICE, 2013], findings reported in this study point to the centrality of the cognitive control domain as a candidate mechanism behind the RRB and therefore as a potentially viable target for treatments aimed at reducing these behaviors.…”
Section: Discussionmentioning
confidence: 82%